Declining Enrollment in M.A. English Literature under the Semester System: A Case Study of Mahendra Multiple Campus, Nepalgunj - Adhikary, Ramesh Prasad (Academia Research Journal, 2025)
This study investigates the notable decline in enrolment in the Master of Arts (M.A.) in English Literature programme at Mahendra Multiple Campus, Nepalgunj, following the implementation of the semester system under Tribhuvan University (TU). While the semester system was introduced to enhance academic quality through continuous assessment, timely evaluations, and global alignment of higher education structures, its impact on certain disciplines—particularly in the humanities—has been contentious. The primary objectives of this research were to document changes in enrolment trends before and after the adoption of the semester system, to identify factors contributing to the decline from both student and faculty perspectives, and to propose strategies for revitalising the programme. The study employed a descriptive case study design, integrating quantitative analysis of institutional enrolment records with qualitative insights from structured student questionnaires and semi-structured faculty interviews. The student population comprised all individuals enrolled in the four active semesters (N = 46), while faculty participants were purposively selected based on their teaching experience in the department. The findings reveal a substantial drop in enrolment—from over 50 students per year under the annual system to between 9 and 15 students per semester under the semester system. The most frequently cited reasons by students include migration abroad before completing bachelor’s degrees (60%), lack of guaranteed employment prospects after graduation (40%), rigid attendance requirements limiting working students (30%), and prolonged undergraduate completion due to examination delays (20%). Faculty emphasised structural issues, particularly the phase-out of the Proficiency Certificate Level (PCL), and the growing student preference for market-oriented disciplines. The study concludes that declining enrolment is the result of intersecting structural, institutional, and socio-economic factors. It recommends flexible attendance policies, curriculum enrichment with market-relevant skills, restoration of academic feeder pathways, and targeted outreach to counteract negative perceptions of humanities education.